EKSISTENSI MASYARAKAT ADAT DI TENGAH REVOLUSI INDUSTRI 4.0 - Hafsah Aqilla; Denta Amelia; Fatiya Rahmah; Arif Budi Abraham; Faizi Faizi (Aceh Anthropological Journal, 2022)
In the last decade, the discussion around the fourth industrial revolution which emphasizes on the automation of all aspects of life has increased. The fourth industrial revolution, which is synonymous with technological sophistication, gives us an idea of a futuristic reality and this is certainly inseparable from large-scale development that must be encouraged. Even so, in the midst of seemingly relentless development, there is a group of people who seem to be deliberately distancing themselves and sticking to customs and traditions. Therefore, despite today's development narrative which is still centered in urban areas, it is important to see the industrial revolution 4.0 that we are experiencing today from the perspective of a group of people who are often referred to as Indigenous Peoples. In addition to fighting against urban hegemony, this paper also tries to question the meaning of development and the fourth industrial revolution and its implications for different stakeholders. Indigenous peoples respond to this situation by trying to create a concept of a rival economy against a growth economy with predatory characteristics. This competitive economy is referred to as the Nusantara Economy and prioritizes drastic emphasis on production-consumption activities (degrowth) as well as local, collective and community-based ownership of living space (the commons).Abstrak: Dalam satu dekade terakhir, perbincangan seputar revolusi industri 4.0 yang menekankan pada otomatisasi semua lini kehidupan kian meningkat. Revolusi Industri 4.0 yang identik dengan kecanggihan teknologi memberikan kita gambaran akan realitas yang futuristik dan hal tersebut tentunya tidak terlepas dari pembangunan skala besar yang harus terus digenjot. Meski begitu, di tengah pembangunan yang seakan tanpa henti, ada sekelompok masyarakat yang seperti dengan sengaja menjauhkan diri dan tetap berpegang teguh pada adat dan tradisi. Di tengah narasi pembangunan hari ini yang berpusat di urban, rasanya penting untuk melihat revolusi industri 4.0 yang sedang kita alami hari ini dari kacamata sekelompok masyarakat tadi yang sering disebut juga Masyarakat Adat. Selain melawan hegemoni perkotaan, tulisan ini juga mencoba untuk mempertanyakan kembali apa makna pembangunan dan revolusi industri 4.0 serta implikasinya terhadap berbagai aktor yang berbeda. Masyarakat Adat merespons situasi ini dengan mencoba menciptakan suatu konsep ekonomi tanding terhadap ekonomi pertumbuhan yang berkarakter pemangsa. Ekonomi tanding ini disebut sebagai Ekonomi Nusantara dan mengedepankan penekanan kegiatan produksi-konsumsi secara drastis (degrowth) serta kepemilikan ruang hidup secara lokal, kolektif dan berbasis komunitas (the commons).